Revolutionaries to race leaders : Black power and the making of African American politics - Johnson, Cedric, 1971- (University of Minnesota Press, 2007)
Exploring the major political and intellectual currents from the Black Power era to the present, Cedric Johnson reveals how black political life conformed to liberal democratic capitalism and how the movement's most radical aims were eclipsed by more moderate aspirations. Documenting the historical retreat from democratic struggle, Revolutionaries to Race Leaders ultimately calls for the renewal of popular resistance and class-conscious politics.